Islamic Waqf, Maqashid Shariah, and SDG-11 - Rusydiana, Aam Slamet; Laila, Nisful; Aslan, Hakan (International Journal of Waqf, 2023)
This study aims to determine the opinions and recommendations of experts regarding the waqf model integrated with sustainable development (SDGs) in goal 11, namely sustainable cities and communities. This research will explain the priority of the waqf model in achieving SDG 11 goals by considering Maqashid Shariah indicators. The data were analyzed using the Delphi method to find the main priorities and agreement of the experts. The results show that all variables have been agreed upon by experts. Furthermore, on the SDGs aspect, the environment element is the top priority with an average score of 8.07. In the maqashid shariah aspect, the element of preserving bi'ah (environment) is the top priority with an average score of 7.53. As for the waqf model aspect, the Waqf & Sukuk model is the top priority with an average score of 7.73. This research can be utilized as a reference in the implementation of waqf models that can support the realization of the eleventh goal of the SDGs by considering Maqashid Shariah with priorities according to the findings. This research is the first to comprehensively calculate the experts' assessment of waqf models for the achievement of SDG 11 using the Delphi method and its priority recommendations.